Analisis Perbandingan Kinerja Keuangan Pemerintah Daerah Kabupaten Dan Kota Di Provinsi Kalimantan Utara Sebelum Dan Sesudah Pemekaran Daerah - Bertilia Lina Kusrina; Fikriyyah Agustina; Gatot Subiyakto; Ira Phajar Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
One measure of how well newly independent regions manage their territories is how well they function financially. North Kalimantan Province was officially formed on November 16, 2012, with the signing of Law No. 20/2012 on the Establishment of North Kalimantan Province. The purpose of this study is to compare the financial performance of districts and cities in North Kalimantan Province before and after regional expansion (2010-2013) and after regional expansion (2014-2017). The research method used is quantitative method. The revenue growth ratio and PAD effectiveness ratio differ between before and after regional expansion, as determined by the Wilcoxon Signed Rank Test. Meanwhile, there is no difference between the ratio of regional financial dependence and regional financial independence, the degree of decentralization, or the degree of decentralization. Differences in the ratio of expenditure growth to GRDP, the compatibility of operating expenditure, and the compatibility of capital expenditure can be seen in the ratio of regional expenditure both before and after the division. Keywords: Financial Performance, Regional Expansion, Regional Autonomy, Local Revenue, Financial Gap